A expansão da educação superior privada no Brasil por meio do FIES - Tarcísio Luiz Pereira; Silvia Helena Andrade de Brito (EccoS – Revista Científica)
This article aims to discuss how FIES was important both for the expansion and growth of business groups in private higher education in Brazil, mainly from the second half of the 1990s until the first decade of the 21st century. In order to do that, it presents research data about management actions taken by a private IES (Union of Educational Institutions of the State of São Paulo - UNIESP), which had in 2013 about 77.0% of its 130 thousand students using the FIES, according to data published by the magazine is money (number 815 of May 29, 2013). This way, it is analyzed how the actions of the federal government, through the public fund, have been responding and collaborating with the demands of the private sector, and how this transforms the formation of the personal being into merchandise, which must be made available through various access to higher education, on one hand; and, through state financing, its profitability, consolidating the large business groups in the sector.